Soil bioindicators associated to different management regimes of Cedrela odorata plantations - Alarcón Gutiérrez, Enrique; Hernández, Christian; Gardner, Terrence; García Pérez, José Antonio; Caballero, Mayra; Perroni, Yareni; Farnet da Silva, Anne Marie a; Gaime Perraud, Isabelle; Barois, Isabelle (Instituto de Ecología, A.C., 2021)
A good bioindicator of soil health is one that perceives minor changes due to changes in soil management and leads to changes in the processes of the soil ecosystem. The aim was to evaluate the use of soil bioindicators in the determination of the utility of two different Cedrela odorata forestry management systems. The litter and soil samples were collected from the rhizosphere of a monoculture (with no fertilization nor irrigation), and a co-culture (with fertilization and irrigation) stand with Citrus latifolia. The soil and litter bioindicators measured were the activity of acetylesterase (FDA), acid phosphatase (AcPh), alkaline phosphatase (AlkPh), laccase, and the estimation of the potential net rate of carbon mineralization (PNRCM). The results indicated that soil enzyme activities (FDA and phosphatases) in the litter were sensitive to the different management system treatments. Enzymatic activity, per unit dry weight, was higher in litter of co-culture (FDA = 1.05 nkat g-1 AcPh = 1.33 nkat g-1; AlkPh = 03.0 nkat g-1) than in litter of monoculture (FDA = 0.617nkat g-1; AcPh = 0.40 nkat g-1; AlkPh = 0. 983 nkat g-1). Differences in soil total nitrogen content, organic matter (OM) content, and micronutrients were found. In general, the co-culture stand (with fertilization and irrigation) with C. latifolia showed the best results.